1991
DOI: 10.1111/j.1365-2796.1991.tb00441.x
|View full text |Cite
|
Sign up to set email alerts
|

Screening for haemochromatosis: prevalence among Danish blood donors

Abstract: Hereditary haemochromatosis is an autosomal recessive disease that is genetically expressed by excessive accumulation of iron in the tissues, resulting in cirrhosis, diabetes mellitus, cardiomyopathy and hypogonadism. As the disease may be diagnosed before the appearance of symptoms, and prevented by repeated phlebotomies, there are strong implications for adoption of a screening procedure. Determinations of transferrin saturation (TS) and serum ferritin concentration (SF) were used to screen 4302 blood donors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
20
0
1

Year Published

1995
1995
1999
1999

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 13 publications
3
20
0
1
Order By: Relevance
“…Complete ethnic background working population of 2 to 3 newly discovered cases per 1,000 information was not available for 393 employees (19.9%). employees falls at the low end of the spectrum of prevalence Analysis of the five newly identified probands revealed that results reported from other population screening studies and four of the five were likely to be of primarily Celtic heritage pedigree analyses, which generally range from 2 to 8 cases because at least two grandparents for each of these probands per 1,000 population [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]31,45,46 (Table 1). Most of these studies originated from Ireland or Wales.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Complete ethnic background working population of 2 to 3 newly discovered cases per 1,000 information was not available for 393 employees (19.9%). employees falls at the low end of the spectrum of prevalence Analysis of the five newly identified probands revealed that results reported from other population screening studies and four of the five were likely to be of primarily Celtic heritage pedigree analyses, which generally range from 2 to 8 cases because at least two grandparents for each of these probands per 1,000 population [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]31,45,46 (Table 1). Most of these studies originated from Ireland or Wales.…”
mentioning
confidence: 99%
“…Settlements then dispersed to Belgium, the United Kingto 1:270 (0.37%). 11, 13,15,16,18,48 Family studies using HLA typing to assign the homozygous genotype and not dependent dom, Ireland, Spain, Scandinavia, and Eastern Europe. Later migrations of Celtic descendants to Australia and North on clinical or laboratory evidence of iron overload have estimated prevalence at between 2 and 10 cases per America would explain the prevalence of HHC in these countries.…”
mentioning
confidence: 99%
See 3 more Smart Citations